1996
DOI: 10.1007/bf02505229
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CRABP II, psoriasin and cytokeratin 1 mRNA in human skin diseases

Abstract: In order to confirm and further explore the significance of the overexpression of the CRABP II (cellular retinoic acid binding protein type II) and psoriasin genes in psoriatic versus normal skin, we examined the mRNA expression levels of these two genes by in situ hybridization in skin samples from psoriatic plaques and in one case from the border between a psoriatic plaque and uninvolved skin. Both genes were markedly upregulated in lesional skin, with a shift from low to high expression in the transitional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 18 publications
(16 reference statements)
2
43
0
1
Order By: Relevance
“…The presented sweat protein pattern summarizes the dominant proteins in human eccrine sweat and thus provides useful information for further investigations concerning skin diseases such as atopic dermatitis or psoriasis in which some of the proteins are involved, e.g. psoriasin genes are markedly up-regulated in psoriatic versus normal skin, whereas the expression of the cytokeratin I gene is, in contrast, high in normal skin and decreased in psoriatic skin (34). Regarding apolipoprotein D it has been suggested as a new prognostic factor for cutaneous malignant melanoma (35).…”
Section: Discussionmentioning
confidence: 99%
“…The presented sweat protein pattern summarizes the dominant proteins in human eccrine sweat and thus provides useful information for further investigations concerning skin diseases such as atopic dermatitis or psoriasis in which some of the proteins are involved, e.g. psoriasin genes are markedly up-regulated in psoriatic versus normal skin, whereas the expression of the cytokeratin I gene is, in contrast, high in normal skin and decreased in psoriatic skin (34). Regarding apolipoprotein D it has been suggested as a new prognostic factor for cutaneous malignant melanoma (35).…”
Section: Discussionmentioning
confidence: 99%
“…As already noted, these include inflammatory dermatoses (34) and the response to UV-B-related stress (24), resistance to anoikis, and response to wound healing, where altered signaling pathways have been relatively well defined (23,(35)(36)(37). In these circumstances, induction of Akt, NF-nB, and AP-1 are often critical components.…”
Section: S100a7-and S100a7mentioning
confidence: 99%
“…Various studies have reported a significant increase in psoriasin, hBD-2 and LL-37 in both diseases [51,[68][69][70].…”
Section: Clinical Relevance Of Amps In Inflammatory Skin Disordersmentioning
confidence: 94%
“…Several studies acknowledged the theory [13,16]. Psoriasin, hBD-2 and hBD-3, LL-37, RNase 7 and calprotectin are induced in the psoriatic skin [50,51]. The up-regulation of AMPs expression in the skin of psoriasis patients is considered to contribute to a low rate of infections in psoriatic lesions.…”
Section: Clinical Relevance Of Amps In Inflammatory Skin Disordersmentioning
confidence: 99%